THE INFLUENCE OF THE MATCH MINE TYPE COOPERATIVE LEARNING MODEL ON THE MATHEMATICS COMMUNICATION ABILITY OF CLASS VII STUDENTS AT MTS ANNIZHOMIYYAH JAHA-LABUAN - Ati Adi Yanti (International Journal Multidisciplinary Science, 2024)
This research investigates the effect of the Match Mine type Cooperative Learning model on the mathematical communication skills of class VII students at MTs Annizhomiyyah Jaha-Labuan. The experimental method was used with two groups: the experimental group (which received learning using the Match Mine type Cooperative Learning model) and the control group (which received conventional learning). Data was collected through tests before and after treatment and then analyzed to evaluate the impact of the learning model. The analysis results show that applying the Match Mine type Cooperative Learning model significantly influences students' mathematical communication skills. Students in the experimental group showed better abilities in proposing ideas, reflecting on mathematical concepts, solving problems, and discussing than students in the control group. Thus, the Match Mine type Cooperative Learning model can be an effective alternative in improving students' mathematical communication skills. Teachers should consider using this model in the mathematics learning process because it can increase student engagement, creativity, and learning outcomes.